(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: To describe the clinical and paraclinical characteristics of patients with cesarean section scar defects Subjects and methods: A cross-sectional descriptive study of 63 patients who attended the National Center for Reproductive Medicine, National Hospital of Obstetrics and Gynecology, from August 2020 to March 2021. Describe abnormal clinical symptoms of menstruation after cesarean section and characteristics of surgical scar defects through transvaginal ultrasound. Results: The rate of abnormal menstrual bleeding after cesarean section was 74,6%. The rate of abnormal menstrual symptoms, mainly prolonged vaginal bleeding after menstruation, was 53,2%, menorrhagia was 55,3%, dysmenorrhea was 31,9%, pelvic pain was 59, 6%. Scar defect was seen mainly on the uterus in the posterior position, the morphology had 1 branch. The average length, width and depth of scar were 5,8 ± 2,4 mm, 11,2 ± 4,7 mm, and 4,8 ± 2,0 mm, respectively. The average thickness of the remaining uterine muscle was 4,1 ± 1,6mm (from 1,0mm to 8,3mm). The scar defect size was larger in the group with symptoms of prolonged bleeding after menses and menorrhagia with p < 0,05. Conclusion: Patients with cesarean scar defects had abnormal menstrual rates over 50%. Scar defects were mainly seen on the uterus in the retrograde position, the shape of a single-branch defect, the size of the scar defect was related to the severity of the clinical manifestations.